Principles of German criminal procedure - Bohlander, Michael (London [England] : Hart Publishing, 2021)
"The new edition of this seminal text outlines the fundamental aspects of the German approach to criminal procedure. It explores a wide range of issues from setting out the basic procedural principles to presenting the main players in the criminal justice system, pre-trial investigations, the path from indictment to trial judgment, rules of evidence, sentencing, and appeals and post-conviction review. As far as it is useful for an introductory text, the differences between proceedings against adults and juveniles are highlighted. The theoretical discussion of decision-making and style of judgment writing is supported by practical insights through specimen translations of an indictment, a trial judgment and an appellate judgment by the Federal Court of Justice."--
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Criminal procedure -- Germany; Comparative law; Electronic books